Social rights of children in Europe : a case law study on selected rights - Häusler, Katharina (Brill Nijhoff, 2019)
The Convention on the Rights of the Child has changed the paradigm of how (human rights) law looks at children: from "objects" of protection to full rights-holders of all human rights. Consequently, social rights are not voluntary welfare services but an expression of the dignity and rights of the child. In Social Rights of Children in Europe Katharina Häusler provides a thorough analysis of how these basic social rights are interpreted by the three major human rights bodies on the level of the Council of Europe and the European Union. It thus offers not only an excellent picture of the main lines of interpretation but also of the major gaps and challenges for the realisation of children's social rights in Europe